2018
DOI: 10.1021/acsami.8b11688
|View full text |Cite
|
Sign up to set email alerts
|

CeOx-Decorated NiFe-Layered Double Hydroxide for Efficient Alkaline Hydrogen Evolution by Oxygen Vacancy Engineering

Abstract: As a promising bifunctional electrocatalyst for water splitting, NiFe-layered double hydroxide (NiFe LDH) demonstrates an excellent activity toward oxygen evolution reaction (OER) in alkaline solution. However, its hydrogen evolution reaction (HER) activity is challenged owing to the poor electronic conductivity and insufficient electrochemical active sites. Therefore, a three-dimensional self-supporting metal hydroxide/oxide electrode with abundant oxygen vacancies is prepared by electrodepositing CeO nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(116 citation statements)
references
References 73 publications
4
108
0
4
Order By: Relevance
“…It is well known that layered double hydroxide (LDH)‐based nanomaterials are efficient electrocatalysts for OER, but the catalytic activities for HER are unsatisfactory due to their inferior in converting the absorbed H to hydrogen gas. [ 149 ] To overcome this challenge, Zhao and co‐workers [ 135 ] prepared CeO x nanoparticles on NiFe LDH nanosheets (NiFe LDH/CeO x ) via electrodeposition process (Figure 14c). EIS measurement demonstrated that the designed NiFe LDH/CeOx exhibited the lowest charge‐transfer resistance relative to other measured samples because of the oxygen vacancies at their interface between NiFe LDH and CeO x changed the charge distribution, local electric field and increased the charge carrier concentration.…”
Section: Electrochemical‐related Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that layered double hydroxide (LDH)‐based nanomaterials are efficient electrocatalysts for OER, but the catalytic activities for HER are unsatisfactory due to their inferior in converting the absorbed H to hydrogen gas. [ 149 ] To overcome this challenge, Zhao and co‐workers [ 135 ] prepared CeO x nanoparticles on NiFe LDH nanosheets (NiFe LDH/CeO x ) via electrodeposition process (Figure 14c). EIS measurement demonstrated that the designed NiFe LDH/CeOx exhibited the lowest charge‐transfer resistance relative to other measured samples because of the oxygen vacancies at their interface between NiFe LDH and CeO x changed the charge distribution, local electric field and increased the charge carrier concentration.…”
Section: Electrochemical‐related Reactionsmentioning
confidence: 99%
“…Reproduced with permission. [ 135 ] Copyright 2018, American Chemical Society. d) Adsorption energies of H 2 O molecules on the surfaces of Ni 3 N and Ni 3 N 1 −x .…”
Section: Electrochemical‐related Reactionsmentioning
confidence: 99%
“…The intermediate product of NiFe‐LDH@3DGF (Figure b) exhibit that the NiFe‐LDH nanosheets directly grow on the porous channels of graphene foam and uniformly form an intersected network. The phase information of NiFe‐LDH@3DGF can be obtained by XRD pattern (Figure S2), which corresponds to the structure of NiFe‐LDH (PDF#40‐0215) . Through the low‐temperature phosphating reaction, NiFe‐LDH was converted into phosphide NiFe‐P, without any morphological change and destruction (Figure c, d).…”
Section: Resultsmentioning
confidence: 99%
“…The phase information of NiFe-LDH@3DGF can be obtained by XRD pattern ( Figure S2), which corresponds to the structure of NiFe-LDH (PDF#40-0215). [43,44] Through the low-temperature phosphating reaction, NiFe-LDH was converted into phosphide NiFe-P, without any morphological change and destruction (Figure 2c, d). The XRD pattern of NiFe-P@3DGF shown in Figure S3 reveals that the peaks at 40.8°, 44.5°, 47.6°, 54.3°, and 54.8°are indexed to (111), (201), (210), (300), and (211) facets, very close to that of Ni 2 P (PDF#74-1385), which indicates that NiFe-P component actually can be confirmed to be the Fe doped Ni 2 P single-phase substance due to the introduction of Fe atoms, rather than multiphase structure.…”
Section: Microstructure Characterization Of Nife-p@3dgfmentioning
confidence: 99%
“…[21][22][23][24][25][26] Recently, several groups reported the improvement of the performance of catalysts in hydrogen and oxygen generation by doping cerium into the host catalyst or constructing a heterogeneous structure between CeO 2 and the active catalysts. [27][28][29][30][31][32][33][34] For instance, CeO 2 -cluster-doped NiO shows better performance in the OER than CeO 2 cluster surface-loaded NiO, due to promoted oxygen storage capacity and modied electronic structure of the active sites. 35 The promotion of FeOOH catalysts for OER by the integration of CeO 2 has been demonstrated due to the larger oxygen storage capacity of CeO 2 and electron interaction between CeO 2 and electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%